2003
DOI: 10.1016/s0045-6535(03)00486-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of a multi-layer column device for study on leachability of nitrate in sludge-amended soils

Abstract: This paper described a multi-layer column device constructed with six cylindrical polythene tubes with installation of Rhizon soil moisture samplers (Rhizon SMS). The feasibility of using the column device to collect soil solution and percolate and to monitor leachability of nitrate in two sludge-amended soils was evaluated under glasshouse conditions. The soil moisture sampler in the device was demonstrated to be a non-destructive, simultaneous, sequential, convenient and rapid sampling tool for multiple-site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A schematic diagram of the soil microcosm system (measuring 60 cm in length and 35 cm in diameter), which was modified from the diagram published by Yu et al (2007) and Luo et al (2003), is shown in Fig. 1.…”
Section: Construction Of Soil Columnsmentioning
confidence: 99%
See 1 more Smart Citation
“…A schematic diagram of the soil microcosm system (measuring 60 cm in length and 35 cm in diameter), which was modified from the diagram published by Yu et al (2007) and Luo et al (2003), is shown in Fig. 1.…”
Section: Construction Of Soil Columnsmentioning
confidence: 99%
“…To concessive monitor the soil N dynamic during rice growth season, we modified the experiment device from the diagram published by Luo et al (2003) and Yu et al (2007), and found it was very suitable to study the leaching loss of nutrients as well as hazard materials in soil. The TN in the soil solution from WD treatments was much lower than the TN from FI treatments (Fig.…”
Section: N Dynamics and Leaching In Paddy Soilmentioning
confidence: 99%
“…64, 2018, No. 3: 95-101 concentration in the B-amended soil was similar or lower than at sowing, suggesting that most N released from biosolids was taken up by plants, greatly reducing leaching risk (Luo et al 2003). Plant growth, grain yield and N content.…”
Section: Resultsmentioning
confidence: 93%
“…The acrylic sampler has the advantage of being left in place throughout the entire experiment causing minimal disturbance to the local benthic flow patterns (Cappuyns et al 2004;SeebergElverfeldt et al 2005). The porewater collected this way was ready for analysis without the need of further preservation (Luo et al 2003;Seeberg-Elverfeldt et al 2005). Profiles from March and April presented here correspond to the upper limit of the SGD seepage area, since for the other months the porewater profiles were taken within the seepage face, close to the peak discharge ( Fig.…”
Section: Site Description and Sample Collectionmentioning
confidence: 99%